Mitigation of Initial Cardiodynamic Effects of the S1P1 Receptor Modulator Ponesimod Using a Novel Up‐Titration Regimen. (30th September 2016) - Juif, Pierre‐Eric; Hoch, Matthias; Vaclavkova, Andrea; Krause, Andreas; Bush, Jim; Dingemanse, Jasper
Abstract: Ponesimod, a potent selective sphingosine‐1‐phosphate receptor 1 modulator, leads to a reduction in circulating total lymphocyte count and transient decreases in heart rate (HR). Based on a modeling and simulation approach, this study was conducted to investigate whether a gradual up‐titration regimen may mitigate these cardiodynamic effects. In this double‐blind, placebo‐controlled, randomized, 2‐way crossover study, 32 healthy participants (15 males) received placebo on day 1 followed by multiple‐dose administration of either ponesimod or placebo (ratio 3:1). Ponesimod was administered alternately using regimen A (incremental dose increase from 2 to 20 mg in 9 steps) or B (10 mg for 7 days followed by a single‐dose administration of 20 mg). Cardiodynamic (Holter and 12‐lead ECG), pharmacokinetic, pharmacodynamic (total lymphocyte count), and safety variables were assessed. After first‐dose ponesimod administration (day 2), a transient decrease in HR was observed (nadir 2‐3 hours postdose, back to predose values within 4‐5 hours) of approximately 6 and 12 beats/min (bpm) (mean) following regimens A and B, respectively. On day 2, occurrence of HR <45 bpm, HR decrease from baseline of over 20 bpm, PR interval ≥200 milliseconds, or PR interval increase from baseline >20 ms, was lower following regimen A than B (14 vs 43 events). During the course of the study, incidence of HR <45 bpm was lower following regimen A than B (20 vs 58 events). Fewer participants reported adverse events following regimen A than B. Pharmacokinetics and pharmacodynamics were similar between the regimens. The novel gradual up‐titration with ponesimod markedly mitigated initial cardiodynamic effects.